The Related Role of Anxiety and Parental Resilience on the Aggressive Tendencies of Preschool Children during the COVID-19 Pandemic - Evrim Durgut Şakrucu; Haktan Demircioğlu (MDPI AG, 2024)
In this study, we aimed to determine the related role of anxiety and parental resilience on the aggressive tendencies of preschool children during the COVID-19 pandemic. The study sample comprised a total of 293 parents with children aged 4-6 years. Relationships between Preschool Anxiety Scale, Aggression Orientation Scale, and Brief Resilience Scale total and subscale scores were evaluated using Pearson and Spearman correlation analysis. The results of this study show that there is a positive relationship between children's aggression tendencies and anxiety levels. We observed weak to moderate correlations between parents' resilience scores and the children's aggression and anxiety scores. Although linear regression analysis indicated no significant effect of parental resilience on children's aggressive tendencies, anxiety levels may be related. In addition, study results showed that the physical aggression tendencies of children differed according to their age and the number of children in the family, albeit at a low level. Further studies are needed to identify factors associated with aggression in preschool children.